2019
DOI: 10.1590/fst.20718
|View full text |Cite
|
Sign up to set email alerts
|

Anti-adipogenic effect of a turmeric extract-loaded nanoemulsion in 3T3-L1 preadipocytes and high fat diet-fed mice

Abstract: We investigated the effects of a turmeric extract-loaded nanoemulsion (TENE) on lipid accumulation in 3T3-L1 adipocytes and in mice fed a high fat diet (HFD). The accumulation of intracellular lipid in 3T3-L1 adipocytes was significantly inhibited by TENE, according to Dil red D and Nile Red staining. This inhibitory effect of TENE on adipocyte differentiation was associated with lower expression levels of the adipocyte-specific genes, PPARγ, aP2, and C/EBPα. On HepG2 hepatocytes, TENE attenuated palmitate-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…In contrast to animal proteins, consumption of soy protein has been found in numerous studies to be adversely linked with BMI. Our findings, however, indicated that there was no evident change in BMI between mice fed milk protein or mice fed plant protein 5‐35 . Further, our findings showed that mice fed plant proteins had lower plasma insulin levels than mice fed milk proteins.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…In contrast to animal proteins, consumption of soy protein has been found in numerous studies to be adversely linked with BMI. Our findings, however, indicated that there was no evident change in BMI between mice fed milk protein or mice fed plant protein 5‐35 . Further, our findings showed that mice fed plant proteins had lower plasma insulin levels than mice fed milk proteins.…”
Section: Discussioncontrasting
confidence: 67%
“…The 3T3‐L1 pre‐adipocytes were seeded on a 96‐well plate at a density of 10 000 cells per well. The cytotoxicity activity of protein hydrolysates against 3T3‐L1 pre‐adipocytes was studied using 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide (MTT) reagent 17 . When cells reached 70–80% confluency, they were treated with varying concentrations of milk and plant protein hydrolysates for 48 h and then incubated in MTT solution for 4 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absorbance of the sample was determined at 570 nm. 7 Three independent experiments were performed, each in triplicate.…”
Section: Cell Viability Assaymentioning
confidence: 99%